Porphyromonas gingivalis Infection Induces Lipopolysaccharide and Peptidoglycan Penetration Through Gingival Epithelium - Takeuchi, Hiroki; Nakamura, Eriko; Yamaga, Shunsuke; Amano, Atsuo (Frontiers in Oral Health, 2022)
Periodontal diseases initiate on epithelial surfaces of the subgingival compartment, while the gingival epithelium functions as an epithelial barrier against microbial infection and orchestrates immune responses. Porphyromonas gingivalis is a major pathogen of periodontal diseases and has an ability to penetrate the epithelial barrier. To assess the molecular basis of gingival epithelial barrier dysfunction associated with P. gingivalis, we newly developed a three-dimensional multilayered tissue model of gingival epithelium with gene manipulation. Using this novel approach, P. gingivalis gingipains including Arg- or Lys-specific cysteine proteases were found to specifically degrade junctional adhesion molecule 1 and coxsackievirus and adenovirus receptor in the tissue model, leading to increased permeability for lipopolysaccharide, peptidoglycan, and gingipains. This review summarizes the strategy used by P. gingivalis to disable the epithelial barrier by disrupting specific junctional adhesion molecules.